Teaching English To Esp (English For Specific Purposes) - nining, nining nining (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
Generally the Students study English â€œnot because they are interested in the English Language or English culture as such, but because they need English for study or work purposesâ€ (Robinson, 1991: 2). In ESP, â€œlanguage is learnt not for its own sake or for the sake of gaining a general education, but to smooth the path to entry or greater linguistic efficiency in academic, professional or workplace environmentsâ€ Basturkmen (2006: 18). This denotes that, the role of ESP is to help language learners to build up the needed abilities in order to use them in a specific field of inquiry, occupation, or workplace. These definitions were stated according to ESP evolution through time, this latter is viewed in more details in the following sections. Keyword: teaching english, english for ESP